Effect of biofuel and soot on metal wear characteristic using electron microscopy and 3D image processing - Karin, Preechar; Amornprapa, Warawut; Khamsrisuk, Phiranat; Budsayahem, Pol ake; Chammana, Pattara; Sriprapha, Kobsak; Hanamura, Katsunori (My University, 2017)
The soot contamination in used engine oils of diesel engine vehicles was about 1% by weight. The soot and metal wear particle sizes might be in the range of 0-1 µm and 1-25 µm, respectively. The characteristics of soot affecting on metal wear was investigated. Soot particle contamination in diesel engine oil was simulated using carbon black. Micro-nanostructure of soot particles were studied by scanning electron microscopy (SEM), transmission electron microscopy (TEM) and laser diffraction spectroscopy (LDS). The metal wear behavior was studied by means of a Four-Ball tribology test with wear measured. Wear roughness in micro-scale was investigated by high resolution optical microscopy (OM), 3D rendering optical technique and SEM image processing method. It was found that the ball wear scar diameter increased proportionally to the soot primary particle size. The effect of biodiesel contamination were also increasing in wear scar diameter.